Implementation of Development Strategy for Halal Tourism Destinations - Zaenuri, Muchamad; Rahayu, Karina Yudi; Iqbal, Muhammad; Elianda, Yunita; Akbar, Ali (Graduate School, Universitas Brawijaya, 2022)
This article was aimed to explain the implementation of the Tourism Department's strategy in developing halal tourist destinations in West Lombok Regency and analyze the factors that influence the strategy implementation. The government of West Lombok Regency has drawn up a strategic plan to address the complexity of the problems that arise in halal tourism. This research used a qualitative method. Data were collected through documentation, observation, and interview techniques. The results showed the implementation of the strategy has been carried out in the form of activities and programs. The tourism destination has been characterized as halal and supported by regulatory clarity, the Islamic Culture Community in West Lombok Regency, which is also attached to the natural conditions that are very supportive and the support of the enthusiastic tourism awareness group (POKDARWIS). However, there are still obstacles, including the lack of a clear concept of halal tourism in West Lombok Regency, the lack of marketing or promotion of halal tourism, as well as inadequate and halal-certified facilities. So the recommendation that needs to be conveyed by the Government tourism office of West Nusa Tenggara is the need to translate the program into various activities in more detail and must involve stakeholders to help standardize and certify.Keywords: Development Strategy, Halal Tourism, Implementation.